2015
DOI: 10.1016/j.physbeh.2015.08.011
|View full text |Cite|
|
Sign up to set email alerts
|

Poor quality of life, depressed mood, and memory impairment may be mediated by sleep disruption in patients with Addison's disease

Abstract: Standard replacement therapy for Addison's disease (AD) does not restore a normal circadian rhythm. In fact, hydrocortisone replacement in AD patients likely induces disrupted sleep. Given that healthy sleep plays an important role in improving quality of life, optimizing cognition, and ensuring affect regulation, the aim of this study was to investigate whether poor quality of life, mood alterations, and memory complaints reported by AD patients are associated with their disrupted sleep patterns. Sixty patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
0
23
1
3
Order By: Relevance
“…One study showed increased prevalence of sleep disturbances in Addison's disease (46), and another indicated that glucocorticoid replacement is permissive for rapid eye movement (REM) sleep (47). One study found that, although PAI had a noteworthy direct effect on QoL, the indirect effect of sleep disruption was significantly greater (48). However, sleep quality in PAI and the impact of various replacement therapies have never been properly studied, and it remains unanswered whether disturbed sleep contributes to deficits in QoL.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…One study showed increased prevalence of sleep disturbances in Addison's disease (46), and another indicated that glucocorticoid replacement is permissive for rapid eye movement (REM) sleep (47). One study found that, although PAI had a noteworthy direct effect on QoL, the indirect effect of sleep disruption was significantly greater (48). However, sleep quality in PAI and the impact of various replacement therapies have never been properly studied, and it remains unanswered whether disturbed sleep contributes to deficits in QoL.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…Recent studies, over a decade later, confirmed these observations, that health-related quality of life is significantly impaired in Addisonian patients compared with the age-matched and gender-matched general population, despite the proper use of the recommended oral hydrocortisone doses (131,132). The mental fatigue, accounting for a significant portion of these patient's poorer quality of life, is characterised by higher prevalence of mood disorders (mainly depression), memory impairment and sleep disorders (133). Similar findings have been reported in patients with Cushing's syndrome after long-term remission, where the health-related quality of life remains impaired regardless of aetiology, presence of hormonal deficiencies and different treatment strategies (134).…”
Section: Is There a Relationship Between Gc-based Therapeutics And Nementioning
confidence: 90%
“…Hydrocortisone administration in the late afternoon or early evening leads to relatively elevated cortisol concentrations during the early part of the night (9), but the medication's short half-life results in cortisol deficiencies during the latter part of the night and the early morning (10). Given the importance of the HPA axis in sleep regulation (4), high night-time cortisol during the early hours of sleep, accompanied by high night-time ACTH and CRH, may be one reason why patients with AD frequently report experiencing disrupted, unrefreshing sleep (11,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, and especially in light of sizable literature describing relationships between irregular HPA axis activity and altered sleep architecture in both psychiatric and healthy samples (16,17,18), it is plausible to suggest that hypo-or hyperactivity of that endocrinological system might play a role in explaining why patients with AD self-report, and objectively experience, poorer sleep quality and more frequent sleep disturbances than healthy controls (11,12,14,19).…”
Section: Introductionmentioning
confidence: 99%